Utilization of Outpatient medical services modeling: an application of structural equation modeling on an urban middle class population with healthcare insurance. - Granero, Mariano; Weisbrot, Mariela; Ricci, Ignacio; Laurenza, Mercedes; Vázquez Peña, Fernando (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: Structural equation modeling (SEM) is a valuable tool for guiding decision-making by allowing researchers to identify relationships between different variables and explain the behavior of more abstract variables. This is particularly relevant in understanding the factors that influence an individual's likelihood of consulting the healthcare system, where demographic, social, and psychological factors play a role.The present study proposes an explanatory model of outpatient medical service utilization in an urban middle-class population with health insurance, examining the relationships between demographic, social, and self-perceived health variables.Methods: A longitudinal prospective cohort study was conducted using a structural equation model. Two cross-sectional surveys were initially conducted at different time points, followed by longitudinal analysis that incorporated the information obtained from both cross-sectional surveys.Results: The use of outpatient medical services was explained in the following order according to their strength of association: CPS (coefficient of 0.57), the use of services in the previous period (0.23), self-perceived health in the last period (-0.15), and family problems from the last period (0.08). The remaining variables did not have a statistically significant association.Conclusions: The completion of the CPS is the variable with the greatest explanatory power for the variability in outpatient health service utilization among urban middle-class individuals with health insurance and high levels of education. This finding could have significant implications for healthcare management, informing strategies to ensure the sustainability of the healthcare system through rational resource allocation.
Keywords: health planning; outpatient care; quality of health care; preventive medicine